Being Non - Muslim In A Shari'a Land : the life stories of Christian Policewomen in Aceh, Indonesia - Safira Mustaqilla (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2023)
et,1/adil,c.1